The Cambridge handbook of information technology, life sciences and human rights / edited by Marcello Ienca [and four others]. - Ienca, Marcello (Cambridge Law Handbooks., 2022)
Debates on the human-rights implications of new and emerging technologies have been hampered by the lack of a comprehensive theoretical framework for the complex issues involved. This volume provides that framework, bringing a multidisciplinary and international perspective to the evolution of human rights in the digital and biotechnological era. It delves into the latest frontiers of technological innovation in the life sciences and information technology sectors, such as neurotechnology, robotics, genetic engineering, and artificial intelligence. Leading experts from the technological, medical, and social sciences as well as law, philosophy, and business share their extensive knowledge about the transformation of the rights framework in response to technological innovation. In addition to providing a comprehensive, interdisciplinary, and international state-of-the art descriptive analysis, the volume also offers policy recommendations to protect and promote human rights in the context of emerging socio-technological trends.